Effect of Foam Roll recovery method on performance in water polo players: a randomized controlled trial - Barrenetxea-García, J.; Nuell, S.; Garai, S.; Murua-Ruiz, A.; Mielgo-Ayuso, J.; Calleja-González, J.; Villarreal, E. S. d. (The Physician and Sportsmedicine, 2024)
Objectives This intervention study aimed to evaluate how the use of Foam Roller (FR) as a recovery strategy affects water polo performance after a seven-week (28-session) program.